Developing and Sustaining Recovery-Orientation in Mental Health Practice: Experiences of Occupational Therapists - Alexandra Nugent; Nicola Hancock; Anne Honey (Hindawi-Wiley, 2017)
Background/Aim. Internationally, mental health policy requires clinicians to shift from a medical to a recovery-oriented approach. However, there is a significant lag in the translation of policy into practice. Occupational therapists have been identified as ideally situated to be recovery-oriented yet limited research exploring how they do this exists. This study aimed to explore Australian occupational therapists' experiences of developing and sustaining recovery-orientation in mental health practice. Methods. Semistructured, in-depth interviews were conducted with twelve occupational therapists working across different mental health service types. Participants identified themselves as being recovery-oriented. Data were analysed using constant comparative analysis. Results. Occupational therapists described recovery-oriented practice as an active, ongoing, and intentional process of seeking out knowledge, finding fit between understandings of recovery-oriented practice and their professional identity, holding hope, and developing confidence through clinical reasoning. Human and systemic aspects of therapists' workplace environment influenced this process. Conclusions. Being a recovery-oriented occupational therapist requires more than merely accepting a specific framework. It requires commitment and ongoing work to develop and sustain recovery-orientation. Occupational therapists are called to extend current leadership activity beyond their workplace and to advocate for broader systemic change.